APLIKASI KOMPRESI SMS BERBASIS JAVA ME DENGAN METODE KOMPRESI LZW-HUFFMAN - Dessyanto Boedi P; Heru Cahya Rustamaji; Muhammad Arif Nugraha (Jurusan Teknik Informatika, 2009)
Along development of epoch, people requirement of information and communication technology also increases.One of communication technology is cellular or known as HP ( handphone). HP has standart communicationfacility, SMS (Short Message Services), that applied to send short message in the text form. SMS which in the text form limited to 160 characters 7-bit GSM ( Global of System for Mobile) standard at a message in once sends, if writing more than 160 characters the message must be divided to become several messages, so that the cost will be multiplied with number of the messages.Limitation oftentimes be obstacle in communicating. Compression very useful when data too big but need to be kept in limited place or data will be sent through a communications channel having limited bandwidth. LZW ( Lempel-Ziv-Welch) and Huffman is famous and reliable method for text compression. Therefore appear an idea to built a SMS compression application bases on Java ME with LZW-Huffman compression method, where this application expected will become user choice which wish to increase effectivity SMS communication technology applies, in this case user can write text more than 160 characters in one messages, so that SMS cost totally can be depressed to become cheaper. This application development applies RUP/UP ( Rational Unified Process orUnified Process) methodologies combined with Reverse Engineering. This also applies Java language with Netbeans IDE 6.0 Tools. With this SMS compression application, supossed can help user increasing SMS communication applies effectivity, in this case user can write text more than 160 characters in one messages, so that SMS cost totally can be depressed to become cheaper.